1994
DOI: 10.1007/bf00195914
|View full text |Cite
|
Sign up to set email alerts
|

Disposition kinetics of buspirone in patients with renal or hepatic impairment after administration of single and multiple doses

Abstract: The single dose and steady-state pharmacokinetics of buspirone and its metabolite 1-pyrimidinyl piperazine (1-PP) have been evaluated in normal volunteers and patients with renal or hepatic impairment, using a parallel group design, with assignment of patients to study group on the basis of the degree of renal (mild, moderate, severe) or hepatic (compensated or decompensated) impairment. Each healthy volunteer or patient received a single dose of 10 mg buspirone on Day 1 of the study, and starting 36 h after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Consistent with these findings are the results of single [7] and multiple-dose [21] studies which demonstrated that subjects with hepatic impairment exhibit increased systemic exposure and longer tl/2 values for NEF, HO-NEF and mCPR Subjects in the three treatment groups in the present study had normal liver function which, in the absence of an effect of renal impairment, explains why the pharmacokinetics of nefazodone and its two metabolites were comparable among groups. The lack of significant effect of renal impairment on systemic exposure or elimination of nefazodone and its metabolites is consistent with observations for other drugs which are eliminated mainly by hepatic metabolism, such as buspirone [22] and the selective serotonin reuptake inhibitor drugs, fluoxetine [23] and sertraline [24]. Further findings in this study are more related to drug metabolic capacity than renal function.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with these findings are the results of single [7] and multiple-dose [21] studies which demonstrated that subjects with hepatic impairment exhibit increased systemic exposure and longer tl/2 values for NEF, HO-NEF and mCPR Subjects in the three treatment groups in the present study had normal liver function which, in the absence of an effect of renal impairment, explains why the pharmacokinetics of nefazodone and its two metabolites were comparable among groups. The lack of significant effect of renal impairment on systemic exposure or elimination of nefazodone and its metabolites is consistent with observations for other drugs which are eliminated mainly by hepatic metabolism, such as buspirone [22] and the selective serotonin reuptake inhibitor drugs, fluoxetine [23] and sertraline [24]. Further findings in this study are more related to drug metabolic capacity than renal function.…”
Section: Discussionsupporting
confidence: 77%
“…Unlike the azapirones (eg, buspirone, gepirone, tandospirone), PRX‐00023 has high affinity for only the 5‐HT1A receptor. The high affinity of PRX‐00023 for the 5‐HT1A receptor (K i ≅ 5–11 nM), combined with minimal binding to other receptors such as alpha‐1 (K i ≅ 1600 nM), alpha‐2 (K i ≅ 3000 nM), and dopamine D2 (K i > 2000 nM), may explain the minimal vasoactive effects and other adverse effects relative to buspirone 9 , 10 . In addition, PRX‐00023 cannot be converted to the alpha‐2 antagonist 1‐(2‐pyrimidimyl)‐piperazine, which has been linked to cardiovascular effects 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity of PRX-00023 for the 5-HT1A receptor (K i ≈ 5-11 nM), combined with minimal binding to other receptors such as alpha-1 (K i ≈ 1600 nM), alpha-2 (K i ≈ 3000 nM), and dopamine D2 (K i > 2000 nM), may explain the minimal vasoactive effects and other adverse effects relative to buspirone. 9,10 In addition, PRX-00023 cannot be converted to the alpha-2 antagonist 1-(2-pyrimidimyl)-piperazine, which has been linked to cardiovascular effects. 11 Based on these better selectivity profiles, these investigations were conducted to evaluate the tolerability of a range of single and multiple doses of PRX-00023 with a few titration steps in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buspirone is an anxiolytic which is pharmacologically distinct from benzodiazepines. The pharmacokinetics of buspirone have been studied in patients with CKD and in those with ESRD undergoing HD (90,91). Renal impairment has been associated with increased buspirone concentration, however statistically significant differences have not been demonstrated.…”
Section: Buspironementioning
confidence: 99%